The effect of different intensity of exercise on salivary steroids concentration in elite female swimmers - Yazdanparast, B.; Azarbayjani, M. A.; Rasaee, M. J.; Jourkesh, M.; Ostojic, S. M. (Facta Universitatis: Series Physical Education and Sport, 2009)
The purpose of this study was examine to effect of different exercise intensity (low, medium and high) on the salivary concentration of Cortisol and DHEA in elite girl swimmers. 10 young swimmer girls were voluntary selected as subjects. The subjects participated in a 6-week exercise program. Exercise program divided to three time courses. Basic endurance season in the first two weeks, Special endurance season in the second two week and the hard exercise season in the last two weeks. Salivary samples were collected at the end of each two weeks before and immediately after exercise from the study group. Concentrations of salivary steroids determined by using ELISA method .The findings of the research show that: exercise with low, medium and high intensity does not have a significant effect on the concentration of, cortisol, DHEA and the ratio of salivary DHEA: C of elite girl swimmers p>0.05. There is no significant correlation between concentrations with salivary cortisol after exercise with high and low intensity p>0.05. But negative significant correlation was found between concentrations with salivary cortisol after exercise with medium intensity p<0.05. There is no significant correlation between concentrations with ratio of salivary DHEA: C after exercise with low, medium and high intensities p>0.05.In conclusion the result of this study show that salivary steroid not affected by intensity of exercise.